2014
DOI: 10.4238/2014.april.16.4
|View full text |Cite
|
Sign up to set email alerts
|

A tiered barcode authentication tool to differentiate medicinal Cassia species in India

Abstract: ABSTRACT. DNA barcoding is a desirable tool for medicinal product authentication. DNA barcoding is a method for species identification using short DNA sequences that are conserved within species, but variable between species. Unlike animals, there is no single universal DNA barcode locus for plants. Coding markers, matK and rbcL, and noncoding markers, trnH-psbA (chloroplast) and ITS2 (nuclear), have been reported to be suitable for the DNA barcoding of plants with varying degree of success. Sixty-four accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The objective of their paper was to find the most universal marker for medicinal plant identification, which is different from some of the following examples where barcoding was used to identify selected species from complexes of intended species and their substitutes. Recent research on Cassia [68], Ginkgo [69], Hypericum [70] and many other species [71] has shown great utility in using DNA barcodes for the authentication of ingredients in herbal medicines and related natural health products (NHPs).…”
Section: Sanger Dna Sequencingmentioning
confidence: 99%
“…The objective of their paper was to find the most universal marker for medicinal plant identification, which is different from some of the following examples where barcoding was used to identify selected species from complexes of intended species and their substitutes. Recent research on Cassia [68], Ginkgo [69], Hypericum [70] and many other species [71] has shown great utility in using DNA barcodes for the authentication of ingredients in herbal medicines and related natural health products (NHPs).…”
Section: Sanger Dna Sequencingmentioning
confidence: 99%
“…Intergenic regions are useful sources for InDels, because these regions underwent relatively rapid mutation due to the less evolutionary constraint. Chloroplast DNA markers for authentication have demonstrated their roles in many aspects as shown in previous studies (Little and Jeanson 2013;Purushothaman et al 2014;Moon et al 2016;Vassou et al 2016). The availability of chloroplast genome sequence to develop the novel loci for DNA markers will become greater in many fields of biology.…”
Section: Discussionmentioning
confidence: 94%
“…Although individual DNA barcodes were sufficient to discriminate each species, we strongly recommend using both barcode regions, as suggested for discriminating Scutellaria baicalensis from its adulterants in a previous report, because matK and rbcL did not exhibit unique marker nucleotides for A. erubescens and P. pedatisecta, respectively, and multilocus DNA barcodes are more effective for identification of plant species (Stoeckle, 2003;Guo et al, 2011;Purushothaman et al, 2014). In addition to the use of both matK and rbcL barcode regions, we also suggest using phylogenetic analyses to authenticate herbal medicines and their adulterants because phylogenetic clustering provides additional information that can be used for species discrimination on the basis of sequence divergence and co-relationships.…”
Section: Discussionmentioning
confidence: 99%